Penentuan Kadar Zat Kimia Dengan Metode Regresi Non Linier Levenberg-marquardt Melalui Analisa Uji Dylon (indian Corn) Menggunakan Instrument Kolorimeter Berbasis Sensor Warna TCS230 - Joko Catur Condro Cahyono (Teknika, 2009)
The method to determine the concentration of essence is much modification. The expensive instruments reach simple have forced with the difference accuration.  The expensive instruments have highly accuration and difficulty measurement. One of the instruments is the colorimeter have method by calculating the difference of color. The method by calculating the differences of color are not much modification. The commonly of the methods are by directly equivalent.By the background, then design colorimeter by using color sensor TCS230. The relation of the method between ratio of concentration and ratio of color is Non Linier Regression Levenberg-marquardt. The color sensor TCS230 is equaled the equaling instrument Spectrometer Lambda EZ 201. The equal experiments are the precision of instrument, the accurate of instrument, and the reproducibility of instrument.In the accuration experiment, the best method for the color sensing TCS230 is 75.252 %. In the precession experiment, the best method for the color sensor TCS230 is ± 20.863 %. The reproducibility experiment produce that the instruments are reliable for the next experiment.For the best accuration, the data for learning better from equaled instruments Spectrometer Lambda EZ 201. The frequancies of the color sensor are from 1:50 mode, we recommended better 1:1 mode for the best color sensing.